ANALISIS MINAT BELAJAR SISWA KELAS IV SDN 1 CIBEBER PADA PEMBELAJARAN IPAS MELALUI IMPLEMENTASI MODEL DISCOVERY LEARNING - Salma, Syifa (Jurusan Ilmu Pendidikan FKIP Universitas Mataram, 2025)
The purpose of this research is to examine the Discovery Learning model in IPAS education to assess the learning interest of elementary school students, particularly in the material on plant body functions. Discovery Learning is a learning approach that emphasizes the process of self-discovery and is expected to encourage students' interest in learning. The research method used is qualitative. The subjects of the study are fourth-grade students at SDN 1 Cibeber. The research instruments used include observation, observation sheets, questionnaires, and feasibility sheets. The results of the study indicate that students are more active and enthusiastic in learning with the Discovery Learning model. Through observations and questionnaires, students show that their involvement encourages interest in learning IPAS, with an average score of 85%. Thus, the implementation of Discovery Learning is effective in fostering students' interest in learning.